Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/su11216028
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Authentic Leadership on Authentic Followership, Positive Psychological Capital, and Project Performance: Testing for the Mediation Effects

Abstract: This study proposes that leaders and followers in university team projects should have authentic leadership (AL) themselves in order to improve the overall performance of the team project. While previous studies have focused mainly on achieving performance through AL on the firm level, this study endeavored to examine the relationship between university students who are expected to serve in an organization’s human resources department in the future and followers’ project performance (FPP). This study also cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 58 publications
0
24
0
1
Order By: Relevance
“…The findings of this study are aligned with the recent study of (Qu et al, 2019), which found that authentic leaders' high benevolence increases employees' positive outcomes. Likewise, the benefits of a positive ethical climate and the psychological capacities of authentic leaders are not limited for less authentic leaders in an organization but are equally beneficial for subordinates (Tak et al, 2019;Weiss et al, 2018). A comparison between two mechanisms (through contrast analysis) revealed that empowerment leveraged by an authentic leader increases creativity more than a leader-directed supervisor does.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study are aligned with the recent study of (Qu et al, 2019), which found that authentic leaders' high benevolence increases employees' positive outcomes. Likewise, the benefits of a positive ethical climate and the psychological capacities of authentic leaders are not limited for less authentic leaders in an organization but are equally beneficial for subordinates (Tak et al, 2019;Weiss et al, 2018). A comparison between two mechanisms (through contrast analysis) revealed that empowerment leveraged by an authentic leader increases creativity more than a leader-directed supervisor does.…”
Section: Discussionmentioning
confidence: 99%
“…Much research suggests that authentic leaders encourage employees' development, reduce burnout risk, promote a positive ethical climate, and improve work engagement (Hassan and Ahmed, 2011;Laschinger and Fida, 2014). Moreover, some evidence showed the positive effect of supervisor integrity and authentic leadership on performance (Leroy et al, 2012;Tak et al, 2019). Integrity, emotion management, respect, and a responsible and considerate approach are crucial competencies to manage employees positively and to become positive supervisors (Yarker et al, 2008;Dal Corso et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Leadership is the most influential element on work engagement, because leaders" positive behaviors can establish a healthy work environment in which employees feel motivated and satisfied (Tak et al, 2019). Since the beginning of the twentieth century, the phenomenon of leadership has been one of the most researched topics, yet it remains enigmatic.…”
Section: Leadershipmentioning
confidence: 99%
“…A recent study proposes that leaders in the academic sector should display "authentic leadership" in order to improve the overall performance of their team"s projects. This can also contribute to the sustainable performance of universities (Tak et al, 2019). Dwivedi et al (2020) propose that there should be autonomy in decision-making and a balance between change and stability: "Covid-19 reflected on agility and adaptive governance.…”
Section: Leadershipmentioning
confidence: 99%